Sociolinguistic Exploration: How Mobile Legends Shapes Social Language Variations Among Teenagers - Ferdiyansyah, Ferdiyansyah; Rohaniyah, Jaftiyatur; Bahrudin , Dinar Vincy Yunitaka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the sociolinguistic phenomenon of language variation among Indonesian teenagers influenced by the online multiplayer game Mobile Legends: Bang Bang. Using a qualitative case study approach, data were collected through participant observation and surveys involving 15 teenagers aged 15–25 from Pamekasan, East Java. Guided by Labov’s Variationist Sociolinguistics theory, the research investigates three core issues: (1) the types of language variations that emerge within the Mobile Legends community, (2) the influence of the game on teenagers’ linguistic behavior, and (3) the impact of these variations on their social interactions. Findings reveal that Mobile Legends creates a distinctive linguistic environment characterized by gaming-specific jargon, slang, code-switching, and situational register shifts. These linguistic features reflect a hybrid style shaped by both global digital language and local vernacular practices. Importantly, this language extends beyond the gaming context, permeating daily conversations among peer groups. The use of in-game language serves not only for strategic communication but also as a marker of group identity and belonging. However, the study also identifies potential concerns, such as the normalization of vulgar language and a decline in formal communication norms. Additionally, linguistic variation in gaming contexts contributes to the formation of social hierarchies, reinforces group solidarity, and can lead to exclusionary practices toward non-gamers. These findings highlight the need for educational stakeholders to consider the impact of digital culture on adolescent language development, particularly within the Indonesian context.